The effect of decreasing the frequency of dupilumab administration after the first year on the control of chronic rhinosinusitis - Alali, Saleh; Saleh, Lana M.; Aly, Mohammed G.; AlMukhodher, Sundus; Khougeer, Rabea (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Chronic rhinosinusitis with nasal polyposis (CRSwNP) significantly impacts quality of life. Many studies have shown the effectiveness of dupilumab in controlling CRSwNP using bi-weekly protocol over the first year. However, the effect of spacing the dose beyond the first year remains unclear. This study aims to assess the efficacy of the increasing the interval of dupilumab administration in maintaining the effect achieved in the first year. Methods: This prospective study includes CRSwNP patients receiving dupilumab for over a year who transitioned from a bi-weekly to a four-weekly regimen. Clinical response was assessed using nasal polyp size (NPS), sino-nasal outcome test-22 (SNOT-22), Lund-Mackay score (LMKS), serum immunoglobulin E (IgE) levels, and eosinophilic count at three time points: pre-treatment, during bi-weekly dosing, and after switching to four-weekly administration. Results: A sustained clinical improvement was observed across all time points. NPS showed significant difference F (2, 30) =85.97, p<0.0001, generalized eta squared=0.73. similarly, SNOT-22 scores and LMKS exhibited significant differences F (1.33, 19.95) =58.55, p<0.0001, generalized eta squared =0.69 and F (1.29,19.4) =69.41, p<0.0001, generalized eta squared=0.59 respectively. IgE levels and eosinophilic count also showed significant variation F (2, 30) =101.5, p<0.0001, generalized eta squared=0.6 and F (2, 28) 9.37, p<0.0001, generalized eta squared=0.13. Conclusion: Decreasing the frequency of administration of dupilumab after the first year is associated with a sustained disease control.